Nanomaterial-Based Zinc Ion Interference Therapy to Combat Bacterial Infections - Wei, Yongbin; Wang, Jiaming; Wu, Sixuan; Zhou, Ruixue; Zhang, Kaixiang; Zhang, Zhenzhong; Liu, Junjie; Qin, Shangshang; Shi, Jinjin (Frontiers in Immunology, 2022)
Pathogenic bacterial infections are the second highest cause of death worldwide and bring severe challenges to public healthcare. Antibiotic resistance makes it urgent to explore new antibacterial therapy. As an essential metal element in both humans and bacteria, zinc ions have various physiological and biochemical functions. They can stabilize the folded conformation of metalloproteins and participate in critical biochemical reactions, including DNA replication, transcription, translation, and signal transduction. Therefore, zinc deficiency would impair bacterial activity and inhibit the growth of bacteria. Interestingly, excess zinc ions also could cause oxidative stress to damage DNA, proteins, and lipids by inhibiting the function of respiratory enzymes to promote the formation of free radicals. Such dual characteristics endow zinc ions with unparalleled advantages in the direction of antibacterial therapy. Based on the fascinating features of zinc ions, nanomaterial-based zinc ion interference therapy emerges relying on the outstanding benefits of nanomaterials. Zinc ion interference therapy is divided into two classes: zinc overloading and zinc deprivation. In this review, we summarized the recent innovative zinc ion interference strategy for the treatment of bacterial infections and focused on analyzing the antibacterial mechanism of zinc overloading and zinc deprivation. Finally, we discuss the current limitations of zinc ion interference antibacterial therapy and put forward problems of clinical translation for zinc ion interference antibacterial therapy.